PENGARUH PENDIDIKAN, KEPUASAN KERJA DAN MASA KERJA TERHADAP TURNOVER PADA PT.TELKOM AKSES SINGARAJA - SUDARNAYA, I KETUT; SUARTINI, NI KADEK YULI (GANEC SWARA, 2023)
This research aims to determine the influence of education, job satisfaction and length of service on turnover at PT Telkom Access Singaraja. The sample in this study was 95 people. The data collection techniques in this research are documentation and questionnaires. The analysis techniques used in this research are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, f-test. The results of the research show that: 1) the regression coefficient is negative so it is concluded that education has a negative and significant effect on turnover, 2) the regression coefficient is negative so it is concluded that job satisfaction has a negative and significant effect on turnover, 3) the regression coefficient is negative so it is concluded that length of service has a negative and significant effect on turnover. turnover